One Health surveillance of multidrug-resistant diarrheagenic Escherichia coli in Northeast India - Goyal, Shivani Popli; Das, Samaresh; Dolma, Karma G.; Roy, Swagnik; Dutta, Tapan Kumar; Devi, Rajkumari Mandakini; Meru, Megongusie; Kylla, Hosterson; Lyngdoh, W. Valarie; Hazarika, Suranjana Chaliha; Sarmah, Pallab; Sarangthem, Indira; et al. (Frontiers in Microbiology, 2025)
IntroductionThe emerging antimicrobial resistance (AMR) in diarrheagenic Escherichia coli (DEC) has become a critical public health concern worldwide. The present study provides a comprehensive surveillance report on the distribution and AMR profile of DEC in humans, animals and food across Northeast India using the “One Health” approach.MethodsBetween October 2020 and December 2024, 8,149 stool specimens from hospitals, 20,691 market food and 2,094 animal samples were collected and screened for DEC. Identification of pathotypes and antimicrobial susceptibility testing were performed. Correlation and principal component analyses (PCA) were used to assess linkages of AMR profiles across the three sources.ResultsDEC was detected in 61.2%, 20% and 28.2% of the samples, respectively, with predominance of enteropathogenic E. coli. Geographically, Sikkim exhibited the highest incidence of DEC in hospital samples (63.7%), followed by Mizoram (28.2%), while food surveillance suggested a higher prevalence in Mizoram (54%). AMR profiling revealed a high level of resistance against ampicillin (69.5%), azithromycin (68.4%) and cefoxitin (62%) in human isolates, with 75% classified as MDR/XDR. Food isolates also exhibited higher levels of resistance against ampicillin (83.2%), azithromycin (73.6%) and cephalosporins (46-70.9%), with MDR/XDR prevalence of 73.4%. Similarly, animal isolates showed higher level of resistance against ampicillin (71.6%), azithromycin (52%), cephalosporins (42.8-64%) and tetracycline (50.5%) with MDR/XDR prevalence of 88.2%. Emerging resistance against carbapenems in the three different sources has also been detected. Correlation analysis revealed a strong link between AMR patterns in humans and food (r = 0.95). Principal component analysis further corroborated the interaction between humans, food and animals DEC.DiscussionThis study highlights the widespread burden of DEC and the alarming rise of MDR/XDR strains across humans, food and animals in Northeast India. The overlapping AMR patterns suggest shared reservoirs and transmission pathways, emphasizing the urgent need for stringent antimicrobial stewardship, a systematic surveillance system and improved hygiene practices to mitigate the spread of MDR-DEC.